The Function of Legislation in Ensuring Legal Certainty and Good Governance - Firial Tiara Efriliani; Sandra Laudya Angelina; Risa Dewi Oktaviani; Muhammad Usman; Irsyaf Marsal (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This paper examines the strategic role of legislation in supporting governance and shaping the structure of Indonesia's legal system based on the prevailing hierarchy. Regulations are understood as instruments that not only provide direction for government action but also set boundaries so that state power is not exercised arbitrarily. In addition, regulations serve to reinforce the relationship between the state and society, so that every citizen obtains legal certainty, which is the main basis for the protection of their rights. Using a literature review approach, this paper examines how harmoniously structured regulations can create sustainable legal stability. The analysis shows that the quality of regulations greatly affects the effectiveness of governance, as a poorly coordinated legal system often leads to policy disharmony, inefficient program implementation, and a decline in public trust. Therefore, understanding the function of regulations and their position in the legal hierarchy is important to ensure the creation of a solid rule of law.Â